FLUOROSE POR INGESTÃO VOLUNTÁRIA DE PASTA FLUORETADA APÓS OS 5 ANOS DE IDADE: RELATO DE CASO E DISCUSSÃO DA IMPORTÂNCIA DA EDUCAÇÃO EM SAÚDE BUCAL NA 1A INFÂNCIA - Venturin, Fernanda (2022)
Introduction: Concerns about children’s intake of fluoride toothpaste are limitedto infancy due to the risk of fluorosis in the permanent anterior teeth, but theeducational process to ensure safety for the entire dentition has been neglected.Objective: To report a case of dental fluorosis in canine, premolar and 2nd molarteeth caused by voluntary ingestion of fluoride toothpaste. Case report: A 12-year-old patient, 65 kg, search dental care due to dissatisfaction with the color ofthe posterior teeth. It was diagnosticated that the superior and inferior canine,premolar and second molar teeth had fluorotic opacities, and the other teeth aresound. Among the possible causes, the main one was the way the child startedbrushing their teeth after 5 years of age. It was reported that she voluntarilybrushed her teeth 6x/day without spitting. Analyzes of the fluoride concentrationin the water consumed by the patient and in the toothpastes used were performed.A urinary fluoride excretion test by the patient, requesting her to brush her teethby spitting out or swallowing all the toothpaste in use, was made. Results: Fluorideconcentration in the water was 0.74 mg F/L and 1,357 and 1,426 mg F/kg in thetoothpastes pastes used. In urine test, 0.90 and 1.35 mg F were found, respectively,spitting or swallowing the toothpaste after brushing. It was estimated that from 5years of age, the child was submitted a dose of 0.17 mg F/day/kg of body weight,which is 2.4 times the upper limit for an acceptable fluorosis. Conclusion: Thereported case suggests that it is a consequence of the failure of the health educationprocess in early childhood regarding the rational use of fluoride toothpaste.